Antimicrobial use and resistance in commercial village chickens: a study on knowledge and practices among farmers - M. I., Nur; Abdul Kadir, Arifah; Nik Mohd Azmi, Nik Mohd Faiz; Mansor, Rozaihan (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2018)
The growth of commercial village chicken farming in Malaysia is improving with the involvement of new farmers due to its huge potential. A study was carried out in selected states of Malaysia to determine the practice of antimicrobial usage, the level of awareness on antimicrobial resistance (AMR) among the commercial village chicken farmers, and to identify the factors that are associated with the level of awareness on AMR among farmers. Questionnaire was distributed to the farmers via two methods, farm visit and online survey. The results from this study showed that majority (77%) of the commercial village chicken farmers use antimicrobial in their farms. Most of the farmers have an average level of awareness on AMR (56%). The results also suggested that there is association between the education level with the level of awareness on AMR (P<0.05). Therefore, the level of awareness among farmers was only moderate which means the farmers were not fully aware of AMR.